La evaluación y acreditación de la educación superior ecuatoriana y la producción editorial - Álvarez Rodas, Luis (2014)
This article exposes the features of editorial production in public and private universities in Ecuador, in the context of evaluation and quality assurance in higher education, using two different types of material and data: a. A review of the data on book production, titles and areas of knowledge; b. UPS’ accreditation experience with indicators on scientific research, regional research and refereed books. By doing this, we have checked that editorial production has increased and that social sciences prevail in editorial production are in social sciences. Finally, we foresee that the overvaluation of indexed articles and topological restrictions of peer-reviewed books will discourage the development of university editorials. The hypothesis is as follows: the evaluation and accreditation model will be able to stimulate the editorial production and improve research indicators to the extent that it assigns greater valuation to peer-reviewed books and expands its typology.